As vozes e as visões dos catadores de materiais recicláveis sobre o meio ambiente - Rosa, Bárbara Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The aim of our research is to understand how the cooperative Recyclable Materials Collectors of the Cooperative of Franca and Region (COOPERFRAN) siginificam the environment. We resort to literature, go deeper on the subject environment, comprising as it is the concept of nature to Adorno and Horkheimer, analyzing how rationality dominates nature transforming it into the capitalist mode of production into a mere commodity. Also relate to the nature view that is permeated by the culture industry, showing that capitalism not only dominates material life, but the imagination, thought and ideas of the subject, creating a false idea of how we relate to nature to discuss this issue, bringing thoughts on how the environment is currently seen use Mészáros. Finazimos the literature on deepening the ethical issue correlacioando with the current environmental problems and perpassamos the Brazilian environmental legislation. The field research included primary and secondary data. The primary data were based on instrumental interviews, observation, and pictures taken by waste pickers. Structured interviews were intended to profile of collectors in 2013, 2014 and 2015 and the semi-structured his reflections on the environmental issue. As for the secondary data is constituted by analyzing documents for themselves collectors, such as Minutes, Bylaws and Articles of Association of Recyclable Materials Collectors Cooperative of France and region (COOPERFRAN). The historical materialist method dialectical underwrote all the research, allowing understand the issue within a historical context and critically, in a perspective of totality. Thus, the research provide insight to discuss environmental issues, working with the act, with the thinking of recyclable material collectors

O objetivo de nossa pesquisa é compreender como os cooperados, da Cooperativa de Catadores de Materiais Recicláveis de Franca e Região (COOPERFRAN) entendem o meio ambiente. Recorremos à pesquisa bibliográfica, aprofundamos a temática do meio ambiente, compreendendo como se constitui o conceito de natureza para Adorno e Horkheimer, analisando como a racionalidade domina a natureza, transformando-a, no modo de produção capitalista, em mera mercadoria. Também relacionamos a visão de natureza que é perpassada pela indústria cultural, mostrando que o capitalismo não domina apenas a vida material, mas também o imaginário, o pensamento e as ideias dos sujeitos, criando-se uma falsa ideia de como devemos nos relacionar com a natureza. Para discutir essa questão, trazendo reflexões sobre como o meio ambiente é visto atualmente, utilizamos Mészáros. Finalizamos a pesquisa bibliográfica, aprofundando a questão ética, correlacionada à problemática ambiental atual, considerando a legislação ambiental brasileira. A pesquisa de campo contemplou dados primários e secundários. Os dados primários foram fundamentados no instrumental de entrevistas, na observação e nas fotografias tiradas pelos catadores de materiais recicláveis. As entrevistas estruturadas tiveram o objetivo de traçar o perfil dos catadores nos anos de 2013, 2014 e 2015 e as entrevistas semiestruturadas observam suas reflexões sobre a questão ambiental. Já os dados secundários se constituíram por meio da análise de documentos dos próprios catadores, como Atas, Regimento Interno e Estatuto da Cooperativa de Catadores de Materiais Recicláveis de Franca e Região (COOPERFRAN). O método materialista histórico dialético embasou toda a pesquisa, possibilitando compreendermos a questão dentro de um contexto histórico, de maneira crítica, em uma perspectiva de totalidade. Assim, a pesquisa oferece subsídios para se...
Keywords: Serviço social; Trabalhadores - Aspectos ambientais; Meio ambiente - Aspectos sociais; Catadores de lixo; Reaproveitamento (Sobras, refugos, etc.); Cooperativas - São Paulo (Estado); Coleta seletiva de lixo